RANCANG BANGUN PROTOTYPE SYSTEM MONITORING KELEMBABAN TANAH MELALUI SMS BERDASARKAN HASIL PENYIRAMAN TANAMAN “STUDI KASUS TANAMAN CABAI DAN TOMAT” - Caesar Pats Yahwe; Isnawaty Isnawaty; L.M Fid Aksara (Informatics Engineering Department of Halu Oleo University, 2016)
Watering is a matter that can not be discharged in maintaining and caring for plants in order to keep the plants thrive. needs enough water greatly affect plant growth. Examples such as chilli and tomato crops that require special attention because if the plant is not getting a good condition, the plants do not grow well, even be fatal for the plant. Monitoring of watering based on Soil Moisture via SMS based microcontroller is one way that can be used in monitoring and caring for the plants remain in good condition. So as to minimize the time and power plant owners in their activities without the direct care of a plant that belongs. By using Arduino UNO as a main controller is programmed to determine the Soil Moisture the plant through the Soil Moisture Sensor FC-28 were planted in the ground and the results of Soil Moisture the plants obtained will be sent to the mobile phone owner of the plant through the medium of SMS is connected to the GSM Shield ATWIN Quad-Band. When the condition of Soil Moisture detection sensors poor crop, then the Arduino UNO will give the command to start the engine Relay for water and do watering plants. The test results of Soil Moisture monitoring via SMS based on the results of watering the plants showed that the Soil Moisture Sensor FC-28 can detect Soil Moisture and tools can be watering when the soil is dry then sms gateway will work automatically to send an SMS to the owner of the plant. The percentage of success of the tool by 93,75%. Keywords— SMS, Arduino UNO, Soil Moisture Sensor FC-28, GSM Shield ATWIN Quad-Band